Hypoplasia of lung a rare entity mimicking as a case of tuberculosis - Singh, Urvinderpal; Mohan, Vinay; Kumar Goyal, Deepak; Muralidharan, Ramaraj; Shailly, Shailly; Poduvattil, Prasanth; Puneet Kaur, Ritu; Abraham, Jebin (International Journal of Medical Research and Review, 2017)
Pulmonary hypoplasia, a congenital malformation, is characterized by incomplete development of the lungs, leading to an abnormally less number or dimensions of bronchopulmonary segments / alveoli resulting in small fibrotic and non-functional lung. It is usually diagnosed in the neonatal period or in early childhood. Hypoplasia may be primary (idiopathic) or secondary. Primary pulmonary hypoplasia, not related to other congenital anomalies is extremely seldom diagnosed in adults. We report the case of a 32-year-old married female with two kids presented to us with chief complaints of cough and fever for past nine months. Chest radiograph showed opacification of the left hemi-thorax with decrease in its size and marked ipsilateral mediastinal displacement with an increase in volume of right lung. After investigations she was diagnosed as a case of left lung primary pulmonary hypoplasia. High level of excellent clinical judgement needed to spot and diagnose this congenital aberration, often wrongly diagnosed in adults. Hence, once confronted with an opaque hemi-thorax in a young person with ipsilateral shift of the mediastinum, differential diagnosis of “lung hypoplasia” ought to be kept in mind.